Introducing new retail products into the market - Bass, Emily Barwick (Kansas State University, 2013)
House-Autry Mills is a food manufacturing company located in Eastern North Carolina. It produces a variety of products including corn meals, breaders, hushpuppies and biscuits. House-Autry Mills has been producing these types of products for over 200 years and is always looking for ways to promote and expand its business. Before House-Autry Mills decides to add a new line of products, it must conduct a lot of research and evaluate the success in this potential market. The purpose of this thesis is to look at the data available, and determine if grits will be a good fit for House-Autry, and for the market in general. Chapter I is an introduction to the entire thesis project. Much of the literature I reviewed deals with successfully bringing new products to the market. It also goes through an eight-step decision making process when determining if the project should be worked on, or if the project should be dropped at various stages. This is Chapter II of the thesis. The Methods and Data Collection section of this thesis is located in Chapter III. This chapter will go through the process of forming a focus group, screening the participants, and determining what types of questions should be asked, based on the feedback that the firm wants to receive. I also look at several data sets collected through Infoscan Resources, Inc. There are two chapters that contain the results. Chapter IV looks at the results found from the data collected, and chapter V looks at the results that were observed during the two focus groups findings. The final chapter is where my conclusion and recommendations are listed. I included the action that House-Autry Mills took, and also my thoughts on that action. The section goes through different recommendations including the market first approached, risk involved in the new product, the benefit of keeping the price competitive, and the eventual expansion of the line.
Keywords: Corn; Grits; Marketing; Flavored grits; Packaged dinners; Product development; Agriculture, General (0473)